Wind energy generation and forecasts: a case study of Darling and Vredenburg sites - Olaofe, Zaccheus Olaniyi (Department of Electrical Engineering, 2016)
This research study presents the wind resource assessment at two potential onshore wind sites at the Western Cape of South Africa for small and large scale wind energy generation. It is anticipated that by virtue of the enormous wind resources prevalent along the South Africa West Coast, it is economical and cost effective to generate electricity from the wind to offset the increasing cost of energy generation from non-renewable sources (coal-fired, nuclear, gas etc.) which are the major source of power generation. Despite the environmental benefit and economic potentials of the wind energy, its variability and the inability to accurately predict (estimate) the long term energy generation potentials usually lead to difficulties in the selection and development of a suitable wind site for any proposed wind farm project(s) in the country.